Pengaruh Kecepatan Akses Dan Brand Ambassador Terhadap Impulse Buying Aplikasi Shopee Pada Mahasiswa UINSU - Angin , Silvia Amelia Perangin; Birahmani, Nur Ahmadi; Jannah, Nurul (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
The following developments in new technology, especially e-commerce, have reached all areas of the general public and businesses in Indonesia where these developments affect existing market conditions resulting in customers having high impulse buying. Impulse buying is the decision to buy an item that is carried out quickly or spontaneously. The following study aims to know and analyze the Effect of Access Speed and Brand Ambassador on Impulse Buying of the Shopee Application to North Sumatra State Islamic University Students. The following research is quantitative research through the population, namely all students of the State Islamic University of North Sumatra. The sample in the following study amounted to 100 respondents through sample assessment techniques using the formula presented by Umar. The techniques used in the following study are descriptive statistical analysis and multiple linear regression. The results of research show that Speed of Access and Brand Ambassadors simultaneously have a positive and significant effect on the Impulse Buying of the Shopee application to students of the State Islamic University of North Sumatra. While partially, Access Speed has a positive and significant effect on the Impulse Buying of the Shopee application to students of the State Islamic University of North Sumatra, the Brand Ambassador has a positive and significant effect on the Impulse Buying of the Shopee application to students of the State Islamic University of North Sumatra.